2013
DOI: 10.1016/j.cub.2013.06.032
|View full text |Cite
|
Sign up to set email alerts
|

Cell-to-Cell Heterogeneity in Lipid Droplets Suggests a Mechanism to Reduce Lipotoxicity

Abstract: Summary Lipid droplets (LDs) are dynamic organelles that collect, store, and supply lipids [1]. LDs have a central role in the exchange of lipids occurring between the cell and the environment, and provide cells with substrates for energy metabolism, membrane synthesis, and production of lipid-derived molecules such as lipoproteins or hormones. However, lipid-derived metabolites also cause progressive lipotoxicity [2]; accumulation of reactive oxygen species (ROS), endoplasmic reticulum stress, mitochondrial m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
150
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 159 publications
(161 citation statements)
references
References 16 publications
(18 reference statements)
10
150
0
1
Order By: Relevance
“…Both the LD protein PLIN2 (Lsd-2) and the last enzyme in triglyceride biosynthesis, DGAT1, are required specifically in glial cells for LDs and also to dampen ROS levels and mitigate oxidative damage in glia and in neuroblasts [27]. The notion that only a subpopulation of cells may need to accumulate LDs in order to protect the entire tissue has also been proposed for non-alcoholic fatty liver disease, where LD abundance is very variable from one hepatocyte to another [125]. In Drosophila , one of the beneficial roles of glial LDs is to store the abundant PUFA linoleate as triglyceride, thus sequestering it away from the membrane phospholipid pool [27].…”
Section: Roles For Lipid Droplets In Managing Cell Stressmentioning
confidence: 99%
“…Both the LD protein PLIN2 (Lsd-2) and the last enzyme in triglyceride biosynthesis, DGAT1, are required specifically in glial cells for LDs and also to dampen ROS levels and mitigate oxidative damage in glia and in neuroblasts [27]. The notion that only a subpopulation of cells may need to accumulate LDs in order to protect the entire tissue has also been proposed for non-alcoholic fatty liver disease, where LD abundance is very variable from one hepatocyte to another [125]. In Drosophila , one of the beneficial roles of glial LDs is to store the abundant PUFA linoleate as triglyceride, thus sequestering it away from the membrane phospholipid pool [27].…”
Section: Roles For Lipid Droplets In Managing Cell Stressmentioning
confidence: 99%
“…It has recently been shown in hepatocytes that the LDs within a given cell or among cells of the same tissue show a remarkable heterogeneity [18]. Thus it has been suggested that the existence of cells containing high lipid levels within a cell population could potentially reduce lipotoxicity to the average cell without impairing overall lipid homeostasis [18].…”
Section: Introductionmentioning
confidence: 99%
“…Everyone who has ever looked at the lipid droplets of different cell lines or tissues quickly realizes that lipid droplets vary within and between cell types in terms of their spatial organization, number and size ( Fig. 2) (for example, see Gocze and Freeman, 1994;Herms et al, 2013;Szymanski et al, 2007). Drosophila S2 cells, for example, carry many small lipid droplets of equal size (Krahmer et al, 2011) (Fig.…”
Section: Are All Lipid Droplets the Same?mentioning
confidence: 99%